Life beyond infection : home-based pastoral care to people with HIV-positive status within a context of poverty. - Magezi, Vhumani (Stellenbosch : University of Stellenbosch, 2006)
Thesis (DTh (Practical Theology and Missiology))--University of Stellenbosch, 2005.